Risk factors for death in children with visceral leishmaniasis. - Márcia Jaqueline Alves de Queiroz Sampaio; Nara Vasconcelos Cavalcanti; João Guilherme Bezerra Alves; Mário Jorge Costa Fernandes Filho; Jailson B Correia (Public Library of Science (PLoS), 2010)
BACKGROUND: Despite the major public health importance of visceral leishmaniasis (VL) in Latin America, well-designed studies to inform diagnosis, treatment and control interventions are scarce. Few observational studies address prognostic assessment in patients with VL. This study aimed to identify risk factors for death in children aged less than 15 years admitted for VL treatment in a referral center in northeast Brazil. METHODOLOGY/PRINCIPAL FINDINGS: In a retrospective cohort, we reviewed 546 records of patients younger than 15 years admitted with the diagnosis of VL at the Instituto de Medicina Integral Professor Fernando Figueira between May 1996 and June 2006. Age ranged from 4 months to 13.7 years, and 275 (50%) were male. There were 57 deaths, with a case-fatality rate of 10%. In multivariate logistic regression, the independent predictors of risk of dying from VL were (adjusted OR, 95% CI): mucosal bleeding (4.1, 1.3-13.4), jaundice (4.4, 1.7-11.2), dyspnea (2.8, 1.2-6.1), suspected or confirmed bacterial infections (2.7, 1.2-6.1), neutrophil count <500/mm³ (3.1, 1.4-6.9) and platelet count <50,000/mm³ (11.7, 5.4-25.1). A prognostic score was proposed and had satisfactory sensitivity (88.7%) and specificity (78.5%). CONCLUSIONS/SIGNIFICANCE: Prognostic and severity markers can be useful to inform clinical decisions such as whether a child with VL can be safely treated in the local healthcare facility or would potentially benefit from transfer to referral centers where advanced life support facilities are available. High risk patients may benefit from interventions such as early use of extended-spectrum antibiotics or transfusion of blood products. These baseline risk-based supportive interventions should be assessed in clinical trials.